2018
DOI: 10.1016/j.ijso.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of differentiated thyroid carcinoma in multinodular goiter patients

Abstract: Background: The prevalence of multinodular goiter in all over the world is high, commonly in developing countries. Incidence of differentiated thyroid carcinoma among patients with multinodular goiter is increased in recent literature. Aim of study: To determine the incidence rate of differentiated thyroid carcinoma among patients with multinodular goiter. Patients and methods: This study is a cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
4
4
2
Order By: Relevance
“…The histopathological reports of studied patients were 10% papillary carcinoma, 3% follicular carcinoma and 3% medullary carcinoma. Our incidence was slightly higher than a study was conducted by Ghadhban in Iraq which showed that 21.7% of patients with nodular goiter had thyroid carcinoma (19) . Our frequency finding is also close to the frequency of differentiated thyroid carcinoma among nodular goiter found by Al-Salamah et al (20) study in Saudi Arabia of 21.3% that was detected by FNA and confirmed with histopathology.…”
Section: Discussioncontrasting
confidence: 74%
“…The histopathological reports of studied patients were 10% papillary carcinoma, 3% follicular carcinoma and 3% medullary carcinoma. Our incidence was slightly higher than a study was conducted by Ghadhban in Iraq which showed that 21.7% of patients with nodular goiter had thyroid carcinoma (19) . Our frequency finding is also close to the frequency of differentiated thyroid carcinoma among nodular goiter found by Al-Salamah et al (20) study in Saudi Arabia of 21.3% that was detected by FNA and confirmed with histopathology.…”
Section: Discussioncontrasting
confidence: 74%
“…The highest numbers of our patients were in the third decade, which was differ from previous study [12], who found that the higher age group affected was 40-49 years. This was attributed to the difference between the studied samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Iraq is an endemic area for goiter, mostly in northern and middle parts [1] because of the lack of iodine in soil and in the water supply. In addition, that most of our patients were females as compared to males: a finding consistent with many previous studies [5,6,[9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…Since previous studies had yielded widely disparate results regarding the frequency of malignancy in MNG, this study was conducted to gather local evidence to improve the management of these patients and to hail TT as the standard treatment option in MNG. The mean age of patients or subjects in our comprehensive study was 42.89 ± 8.75 years, which was comparable to the study done by [13,18]. Our findings were close to those of Imad et al, reporting an 11.2% incidence of cancer in MNG [19].…”
Section: Discussionsupporting
confidence: 90%